2006
DOI: 10.1139/z05-184
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of boreal toad populations in relation to estimated UV-B dose in Glacier National Park, Montana, USA

Abstract: A recent increase in ultraviolet B radiation is one hypothesis advanced to explain suspected or documented declines of the boreal toad (Bufo boreas Baird and Girard, 1852) across much of the western USA, where some experiments have shown ambient UV-B can reduce embryo survival. We examined B. boreas occupancy relative to daily UV-B dose at 172 potential breeding sites in Glacier National Park, Montana, to assess whether UV-B limits the distribution of toads. Dose estimates were based on ground-level UV-B data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Our data on common toads and European midwife toads suggest that exposure to UV‐B is inversely correlated with the probability of infection and that in midwife toads this effect is independent of elevation. Hossack et al (2006) found that the probability of occurrence of western toads in ponds in Glacier National Park (Montana, USA) increased slightly as UV‐B increases. However, they did not test whether Bd or other pathogens were present.…”
Section: Discussionmentioning
confidence: 99%
“…Our data on common toads and European midwife toads suggest that exposure to UV‐B is inversely correlated with the probability of infection and that in midwife toads this effect is independent of elevation. Hossack et al (2006) found that the probability of occurrence of western toads in ponds in Glacier National Park (Montana, USA) increased slightly as UV‐B increases. However, they did not test whether Bd or other pathogens were present.…”
Section: Discussionmentioning
confidence: 99%
“…We found B. boreas breeding in .20 wetlands the year after that wildfire burned an area where extensive surveys had identified only three breeding sites between 1999 and 2002 (B. R. Hossack and P. S. Corn, unpublished data). Hypotheses to explain the apparent attraction of recently burned habitats include (1) the terrestrial environment provides more optimal thermal conditions for juveniles and adults (G. Guscio and L. Eby, unpublished report to USGS), and (2) burned wetlands provide better oviposition habitats (Hossack et al 2006b). However, we found no differences in the temperature of burned wetlands that were used for breeding compared to those that were not used (B. R. Hossack et al, unpublished manuscript).…”
Section: Discussionmentioning
confidence: 99%
“…232 Field studies of the boreal toad in Glacier National Park, Montana, USA, indicate that UV-B exposure does not limit distribution, and breeding was actually higher in high UV radiation habitats. 233 UV radiation has important interactive effects with other environmental stressors, including delayed development rates in frog tadpoles when exposed to UV-B radiation and environmentally realistic concentrations of 4-tert-octylphenol, an estrogenic microbial decomposition product of widely used industrial surfactants, 234 and a seven-fold increase in lethality of UV-B radiation when toad tadpoles were exposed in the presence of nitrite. 235 There is also some evidence that prior exposure to UV radiation may confer resistance to the interactive effects of UV radiation and toxic compounds, a phenomenon known as cotolerance.…”
Section: Amphibiansmentioning
confidence: 99%